Course‐based undergraduate research experiences in a remote setting: Two case studies documenting implementation and student perceptions. Issue 22 (30th October 2020) - Fey, Samuel B.; Theus, Meredith E.; Ramirez, Aaron R.
Abstract: Inquiry‐based components of ecology curricula can be valuable, exposing students to what it means to do science, from conceiving of a meaningful question to effectively disseminating results to an audience. Here, we describe two approaches for implementing independent, remote research for undergraduates enacted in the spring semester of 2020 at Reed College in Portland, OR, reporting case studies from an intermediate‐level ecology course and an interdisciplinary environmental science course. We report on both the challenges as well as the novel opportunities for independent research projects in such a setting, the details of how projects were implemented, the tools and resources that may help facilitate such endeavors, as well as perceptions on the effectiveness of this endeavor by students. As institutes of higher education continue to operate in an online learning environment, we hope these materials help spark a discussion about how to engage in meaningful research experiences as part of coursework in the COVID‐19 era and beyond. Abstract : We report on both the challenges as well as the novel opportunities for independent ecology research projects in a remote learning setting, the details of how projects were implemented, the tools and resources that may help facilitate such endeavors, as well as perceptions on the effectiveness of this endeavor by students.